The X-ray spectral evolution of galactic black hole X-ray binaries toward quiescence - Plotkin, Richard; Gallo, E.; Jonker, P. (Institute of Physics Publishing, 2013)
Most transient black hole X-ray binaries (BHXBs) spend the bulk of their time in a quiescent state, where they accrete matter from their companion star at highly sub-Eddington luminosities (we define quiescence here as a normalized Eddington ratio lx = L 0.5-10 keV/L Edd < 10-5). Here, we present Chandra X-ray imaging spectroscopy for three BHXB systems (H 1743-322, MAXI J1659-152, and XTE J1752-223) as they fade into quiescence following an outburst. Multiple X-ray observations were taken within one month of each other, allowing us to track each individual system's X-ray spectral evolution during its decay. We compare these three systems to other BHXB systems. We confirm that quiescent BHXBs have softer X-ray spectra than low-hard-state BHXBs, and that quiescent BHXB spectral properties show no dependence on the binary system's orbital parameters. However, the observed anti-correlation between X-ray photon index (G) and lx in the low-hard state does not continue once a BHXB enters quiescence. Instead, G plateaus to an average <G> = 2.08 ± 0.07 by the time lx reaches ~10-5. lx ~ 10-5 is thus an observationally motivated upper limit for the beginning of the quiescent spectral state. Our results are discussed in the context of different accretion flow models and across the black hole mass scale.